The Influence of Parenting on Increasing Children's Learning Motivation at Madrasah Ibtidaiyah Darul Hikmah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study was motivated by the phenomenon of low learning motivation among students, which is often caused by a lack of parental attention and excessive use of gadgets in daily life. The purpose of this research was to determine and analyze the influence of parenting patterns on student motivation at MI Darul Hikmah. The study employed a quantitative research design using a survey method involving 15 parents of third-grade students as respondents. Data were collected through questionnaires, interviews, observations, and documentation to obtain a comprehensive understanding of the parenting styles applied and their impact on children’s learning motivation. The findings revealed that parental involvement, guidance, and consistent discipline play a crucial role in shaping students’ motivation to learn. Statistical analysis showed that parenting patterns contributed significantly, accounting for 75% of the variation in student motivation, while the remaining 25% was influenced by other factors such as peer environment, teacher support, and internal student interests. These results emphasize the importance of harmonious communication and active participation of parents in guiding their children’s academic growth. Overall, this research highlights that effective parenting characterized by warmth, attention, and support can significantly improve students’ motivation and learning outcomes at the elementary school level.